Transformative Capabilities in the “Very Old Economy”: Intersectoral Innovation Networks and Learning Alliances - Klaus Schmierl (Revue Interventions Économiques)
The central starting point of the paper is that well-known classical patterns of creating innovations are changing. Innovation processes aren’t originated exclusively within ‘knowledge intensive’ (high-tech) companies any more, but rather mutually between companies of different sectors. This has twofold consequences: On the one hand, the so-called high-tech industry influences non-high-tech branches as well as important suppliers of innovative solutions. On the other hand, the particular requirements and conditions of so-called low-tech branches affect companies of high-tech industries as specific drivers of innovation, too. Considered as a productive force, intersectoral cooperation becomes a main source of innovation, further growing in importance; innovation processes are more and more organized along “distributed knowledge bases” across economic sectors.Therefore, the main thesis of the paper is that today´s knowledge isn’t located within one company originating from one industrial sector any more, but is distributed along the respective value-chain and various sectors. At the same time, the “network” is not only relevant in technology-intensive branches such as IT industry or automotive industry, but becomes also a relevant analytical category for exploring “low-tech” industries and their innovation processes.